Wikibrands : reinventing your company in a customer-driven marketplace - Moffitt, Sean; Dover, Mike (New York : McGraw-Hill Professional, 2011)
Sean Moffitt and Mike Dover show you how to take advantage of the exciting new models of business and technologies--and enthusiastic online communities--one click at a time. --from publisher description
The birth of wikibrands: from ownership, trust, want, preference, love, and now participation--a 150-year fascination -- The Wikibrand rallying cry: the new "mad men" -- A wikibrand road map: taking the high road and avoiding the potholes of a collaborative brand path -- The six benefits of wikibrands: marketing doesn't fit in tiny boxes anymore -- A wikibrand culture: changing your mind-set about the brand customer -- Focus: if I don't know where you're going, I don't want you getting there fast -- Language and content : business gets humanized and presses the "awesome" button -- Incentives, motivations, and outreach: brand fans do it for themselves, not for you -- Rules, guidelines and rituals: this is how we do things, and that's ok -- Tools and platforms: if you build it, they may come -- Community development: the life stages of a wikibrand community -- Internalizing community and channeling Tom Sawyer: the graying line between employee and enthusiast champions -- Community management: how to build a brand garden, not a ghost town -- Measurement and metrics: the imperfect science of monitoring wikibrand performance -- The personal wikibrand: your brand is what they say about you when you're not in the room --The future: brand participation comes alive in the company -- Reference guide: wikibrands extended.
Keywords: Branding (Marketing); Internet marketing; Product management; Wikis (Computer science)